Application of P-median Method in the Location of Logistics Nodes. Issue 1 (June 2020) - Tang, Changyu; Tang, Hongjuan; Jia, Anzhen; Yin, Wang
Abstract: The location of logistics nodes and the concept of P-median method are analyzed in detail. In view of the problem of logistics node location, using P-median theory model, using greedy take-away heuristic algorithm, the Jinan A fruit and vegetable company provides a precise algorithm on the location of logistics node in Jinan. Realizes the rapid solution of the model, removes unqualified address from multiple candidate addresses, and selects the optimal logistics node location option.